2013
DOI: 10.1016/j.jana.2012.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Routine HIV Testing in an Acute Care Hospital in Rhode Island: A Nurse-Initiated Opt-Out Pilot Project

Abstract: The Centers for Disease Control and Prevention (CDC) expanded HIV screening of adults ages 13-64 years in 2006 from risk based to routine. Early detection and treatment improve patient outcomes and prevent disease transmission. This article describes a pilot program in which nurses in an adult inpatient unit at an acute care hospital offer HIV testing to all patients ages 18-64 upon admission through standing orders. The pilot, Standing Orders for Routine Testing (SORT), is a response to changes in state law a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…In those studies, nurse-driven HIV screening tended to increase test offering, acceptance and delivery rates. The current review showed that nurses were in a unique position to reach a large patient population Costello et al, 2013;Hack et al, 2013;Herbert et al, 2012;Knapp et al, 2011;Leblanc et al, 2012). Nevertheless, only half of the studies (56%) had a control group and 4 studies were RCTs which were single-centre or took place in few centres.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…In those studies, nurse-driven HIV screening tended to increase test offering, acceptance and delivery rates. The current review showed that nurses were in a unique position to reach a large patient population Costello et al, 2013;Hack et al, 2013;Herbert et al, 2012;Knapp et al, 2011;Leblanc et al, 2012). Nevertheless, only half of the studies (56%) had a control group and 4 studies were RCTs which were single-centre or took place in few centres.…”
Section: Discussionmentioning
confidence: 77%
“…Only 2 studies, 1 in the United States and 1 in France, analysed the interviews that were conducted with physicians separately from those conducted with nurses. However, Anaya et al (2013) and Costello et al (2013) mentioned that further studies on staff acceptance of nurse-driven HIV screening were under way. Barriers such as staffing, workload and, most likely, the lack of available evidence demonstrating the public health benefits of a routine screening strategy, have hindered its long-term implementation (d' Almeida et al, 2012;McNaghten et al, 2014;White et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike the VCT, routine offer is 'provider-initiated' testing and counselling (PITC). Under this model, an HIV test is recommended for all pregnant women, irrespective of level of risk exposure (Costello et al 2013) and test performed as standard group of tests unless explicitly refused by the woman. The lengthy pretest counselling witnessed with VCT is replaced with concise pretest information that meets the minimum standard for informed consent (Revised Recommendations for HIV Testing of Adults, Adolescents, andPregnant Women in Health-Care Settings 2007, Hensen et al 2011).…”
Section: Introductionmentioning
confidence: 99%